PELAYANAN TERHADAP NARAPIDANA DI RUMAH TAHANAN (RUTAN) TELUK KUANTAN KABUPATEN KUANTAN SINGINGI - Pitri Wili Ramadani; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Service can not be separated from the problem of public interest. The common interest is the correlation with the public interest. Public services arise because of the obligation as a process organizers organizational activities, concerned with the matter of the same personal interests of a group of people or society. But it does not mean that the same interests of a group of people automatically become a public interest. Kuantan Bay (Kuantan) Detention Center is located in downtown Kuantan Singingi Regency located at Jalan Imam Bonjol No.34 Kuantan Bay Market Village and has a total of 20 guards and 6 staff. Detention House of State (Rutan) Teluk Kuantan is now over capacity or no longer ideal between the capacity to the number of prisoners / prisoners. Just imagine, the ideal capacity is only 63 people, but currently crammed with 225 prisoners / prisoners. Ironically again, Men, women and children are forced to be together even in separate cells. Of that number, the number of prisoners / prison men reached 200 men, women prisoner reached 3 people and prisoner 2 children. Based on the background of the above problem, this study aims to find out What are the forms of service to prisoners in prison (Kuantan Singular) Detention Center, Kuantan Singingi How do the prisoners respond to the service at the Kuantan Bay House Detention Center Kuantan Singingi Regency. Keywords: Service to Prisoners, Rumah Tahanan Kuantan Singingi Regency